Distinct motor impairments of dopamine D1 and D2 receptor knockout mice revealed by three types of motor behavior - Nakamura, Toru; Sato, Asako; Kitsukawa, Takashi; Momiyama, Toshihiko; Yamamori, Tetsuo; Sasaoka, Toshikuni (Frontiers in Integrative Neuroscience, 2014)
Both D1R and D2R knock out (KO) mice of the major dopamine receptors show significant motor impairments. However, there are some discrepant reports, which may be due to the differences in genetic background and experimental procedures. In addition, only few studies directly compared the motor performance of D1R and D2R KO mice. In this paper, we examined the behavioral difference among N10 congenic D1R and D2R KO, and wild type (WT) mice. First, we examined spontaneous motor activity in the home cage environment for consecutive five days. Second, we examined motor performance using the rota-rod task, a standard motor task in rodents. Third, we examined motor ability with the Step-Wheel task in which mice were trained to run in a motor-driven turning wheel adjusting their steps on foothold pegs to drink water. The results showed clear differences among the mice of three genotypes in three different types of behavior. In monitoring spontaneous motor activities, D1R and D2R KO mice showed higher and lower 24 h activities, respectively, than WT mice. In the rota-rod tasks, at a low speed, D1R KO mice showed poor performance but later improved, whereas D2R KO mice showed a good performance at early days without further improvement. When first subjected to a high speed task, the D2R KO mice showed poorer rota-rod performance at a low speed than the D1R KO mice. In the Step-Wheel task, across daily sessions, D2R KO mice increased the duration that mice run sufficiently close to the spout to drink water, and decreased time to touch the floor due to missing the peg steps and number of times the wheel was stopped, which performance was much better than that of D1R KO mice. These incongruent results between the two tasks for D1R and D2R KO mice may be due to the differences in the motivation for the rota-rod and Step-Wheel tasks, aversion- and reward-driven, respectively. The Step-Wheel system may become a useful tool for assessing the motor ability of WT and mutant mice.